(untitled) (KASBIT Business Journal, 2021)
The promotion of an ideal body image of women on media has increased the demand among females to achieve the perfect figure. The desire to achieve the perfect figure makes women go through several problems, physical and psychological. Physically, women seeking ideal body image experience an eating disorder. Mentally, they have low self-esteem, depression, and low self-confidence. In contrast, the literature identifies that women having no such desire are safe from such mental and physical problems. This study presents a systematic literature review to address this issue. Findings suggest that mass media and social networking sites are major proponents of ideal body image. Similarly, the existing literature affirms that women encountering such images feel uncomfortable about their bodies and suffer from depression. Further, women having no such strong ideal body images do not go through such mental discomfort. Future research should address how to overcome the ill-effects of the ideal body image. Moreover, different types of psychotherapies can also help women to overcome the mental stress of attaining the perfect figure.